Lung function eight years after neonatal ventilation. Issue 1 (January 1989) - Andréasson, B; Lindroth, M; Mortensson, W; Svenningsen, N W; Jonson, B
Abstract : Forty children who had had artificial ventilation during the neonatal period were studied at the age of 8-10 years with spirometry, the nitrogen washout test, bicycle exercise test, pulse oximetry, electrocardiogram, vectorcardiogram, and chest radiography. The median gestational age at birth was 29 weeks, and the median birth weight was 1310 g. Hyaline membrane disease was the indication for neonatal ventilation in 25 children. Bronchopulmonary dysplasia was diagnosed from radiographs in 11 infants (27%). Airway obstruction was observed in 10 of 11 children who had had bronchopulmonary dysplasia and in nine of 29 children who had not. After inhalation of terbutaline, the forced expiratory volume in one second (FEV1) was significantly increased. General hyperinflation was found in 16 of 17 children with abnormal chest radiographs (eight who had had bronchopulmonary dysplasia and nine who had not). Functional residual capacity was significantly higher in children with abnormal radiographs. Each child had a normal maximum working capacity and a normal electrocardiogram, and all but two had normal vectorcardiograms. Oxygen saturation at maximum work load decreased significantly in both groups of children. The risk of future respiratory problems calls for further follow up of lung function and chest radiography.